Kegiatan Pengabdian Masyarakat Berupa Penapisan Gula Darah dan Hba1C sebagai Penyebab Dermatoporosis pada Lanjut Usia - Tan, Sukmawati Tansil; Gunaidi, Farell Christian; Destra, Edwin; Ramadhani, Kenzie Rafif; Putra, Muhammad Dzakwan Dwi; Sugiarto, Hans (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Dermatoporosis is a chronic skin fragility syndrome common in the elderly, characterized by thinning of the skin that increases the risk of injury, bruising, and delayed wound healing. Chronic hyperglycemia and poor glycemic control have been reported to be associated with an increased risk of dermatoporosis. This community service activity aims to screen blood sugar levels, HbA1c, and dermatoporosis and educate the elderly using the Plan-Do-Check-Act (PDCA) method at Panti Bina Bhakti, South Tangerang. This activity involved 93 elderly participants aged >65 years. Meanwhile, based on the results of the HbA1C examination, 52 people had moderate glycemic control and 24 people had poor glycemic control. The results of the dermatoporosis examination have not been included. Early intervention through education and monitoring of blood sugar levels can reduce the risk of dermatoporosis, improve the health of the elderly's skin, and reduce the burden of health care.